THE SOURCE OF INDIVIDUAL HAPPINESS AND LIFE SATISFACTION: EVIDENCE FROM TURKEY (Third Sector Social Economic Review, 2022)
The purpose of this study is to estimate the most effective sources of contextual and individual on happiness and satisfaction in Turkey. The data used in this study are obtained from three different waves of World Values Survey (WVS) which are 2005-2009, 2010-2014, 2017-2020. By summing all data from these three waves, total sample size has reached 8,766 individuals. Individual happiness was used as dependent variable and measured by a question that defined as the rank of individual happiness (1 =unhappy, 2 =happy, 3 = very happy). In addition, in order to make comparisons, a life satisfaction model was developed with the same explanatory variables used in happiness equation, in which the variable of individuals' life satisfaction (1=not satisfied; 2= dissatisfied; 3=neither satisfied nor satisfied; 4=satisfied; 5=most satisfied) was dependent variable. Because the dependent variables in the study are ordered variables, the main model of this study is the ordered probit model. The findings of this study show that the variables affecting happiness and life satisfaction in Turkey are similar. The most important determinants of happiness and life satisfaction in Turkey are individual and contextual variables such as education, age, marital status, gender, caring for family and friends, being healthy, caring about religion, being satisfied with the financial situation, feeling free, trusting institutions and trusting people. Married individuals are very happy and very satisfied with life compared to unmarried individuals, individuals who care about religion are very happy and very satisfied with life compared to those who do not care about religion. Men and single women have higher levels of happiness and life satisfaction. It was determined that there was a U-shaped relationship between age and happiness, age and life satisfaction. Being satisfied with the financial situation, trusting institutions and people, feeling free affect individual happiness and life satisfaction positively. However, interest in politics in Turkey negatively affects the happiness and life satisfaction levels of individuals.
Keywords: happiness; life satisfaction; subjective-wellbeing; ordered probit